A 2016 social accounting matrix for South Africa with an occupationally disaggregated labour market representation - Dirk van Seventer; Robert H. Davies (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Examining the economy-wide consequences of South Africa following a similar trajectory of labour market polarization to the rest of the world requires an appropriate database for an economy-wide policy analysis framework. This paper describes how a 2015 South Africa social accounting matrix (SAM) was updated for 2016 and expanded to include labour market disaggregation by occupation and some capital market disaggregation. This extended SAM will provide a basis for the construction of an economy-wide modelling framework to examine the implications of likely future growth and structural and technological changes for skills demand in South Africa.
Keywords: E16; C63; J4; O55; 330; Social accounting matrix; national accounts; supply table; use table; labour market